GEOGRAPHY IN THE BIG DATA AGE: AN OVERVIEW OF THE HISTORICAL RESONANCE OF CURRENT DEBATES. - Ferreira, Daniela; Vale, Mário (Geographical Review)
Although much has been written about the challenges of big data, there has been little reflection on the historicity of such debates and what we can learn from it. With this in mind, the aim of this article is to situate the epistemological debates over big data in geography historically. We focus on the three most relevant topics in current discussions around big data that have significant historical resonance, namely its methodological challenges, its scientific value, and its positionality. We conclude by arguing that understanding the historical resonance of current big data debates is helpful to find new ways to question its epistemological consequences.